Mistakes of reason : essays in honour of John Woods - Irvine, A. D.; Peacock, Kent A., 1952-; Woods, John (John Hayden) (Toronto studies in philosophy., 2005)
Over a distinguished academic career, the Canadian philosopher and scholar John Woods has written on a rich variety of topics central to contemporary philosophy. These include the history and philosophy of logic, deviant logics, inductive and abductive reasoning, informal reasoning, fallacy theory, the logic of fiction, epistemology, and abortion and euthanasia. Not only has Woods? work been significant in itself, it has also stimulated others working in these fields. Mistakes of Reason is a tribute to Woods and contains twenty-six new essays by leading Canadian and international philosophers. The essays are accompanied by commentaries by Woods himself, creating a unique dialogue between Woods and his colleagues. Editors Kent A. Peacock and Andrew D. Irvine have grouped the works under the themes of Reality, Knowledge, Logic and Language, Reasoning, and Values. The essays evaluate Woods? work and celebrate the generous contribution that he has made to Canada?s intellectual development over the past forty years.